Psychological distress and its associated factors among caregivers of geriatric patients in Hospital Universiti Sains Malaysia (Hospital USM) - Razali, Nor Hazirah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Psychological distress among caregivers of geriatric patients will create negative consequence to geriatric patients and patient will receive poor quality care from their caregivers. A cross sectional, desc1iptive survey was can·ied out to determine the Psychological distress and its associated factors among caregivers of geriatric patients in Hospital USM. In total 212 caregivers were successfully approaches at Hospital USM. Subjects was randomly selected that fits with inclusion criteria. Data was statistically analysed using SPSS software version 22.0. Statistical significant was considered at p value < 0.05. Majority of the subjects have low psychological distress (60.4 %) and remaining is the high psychological distress (39.6%). There were significant associations between age p < 0.00 I, marital status p = 0.007 and level of education p = < 0.00 I with psychological distress among caregiver of geriatric patients in Hospital USM. Gender p = 0.049 and economic status p = 0.12 were no significant association with psychological distress among caregiver or geriatric patients in Hospital USM. Moreover, researcher also found that there were significant association between age and the selected factors of stressor to the caregivers (physical health).